THE PROCESS OF SCREENING COMPLIANCE OF PATIENTS IN THE TREATMENT OF CHRONIC NON-COMMUNICABLE DISEASES - Khodjieva Gulirano Sayfullaevna (Journal of Medical Genetics and Clinical Biology, 2024)
This article describes the results of a study on the adaptation, implementation and evaluation of the effectiveness of the MyTherapy mobile application in the practice of treating chronic non-infectious diseases in order to monitor treatment and patient compliance. Based on the more pronounced positive dynamics of the therapy itself, the improvement in the quality of life indicator and the indicator of adherence to treatment, it is shown that the use of this mobile application can be a highly effective method of monitoring the therapy of chronic non-infectious diseases when used correctly